Zinc Oxide (ZnO) and solar photocatalytic treatment of leachate - Salwa, Mohd Zaini Makhtar; Naimah, Ibrahim; Azlinda, Abdul Ghani; Ragunathan, Santiagoo (Malaysian Institute of Chemistry, 2008)
Organized by Malaysia Institute of Chemistry, 23rd - 25th August 2007 at Putra World Trade Centre, Kuala Lumpur.